B‐frame velocity aided coarse alignment method for dynamic SINS. Issue 8 (1st August 2018) - Guo, Shiluo; Wu, Miao; Xu, Jiangning; Zha, Feng
Abstract : Dynamic alignment is a challenging issue for the strapdown inertial navigation system (SINS), especially in the case of no Global Position System assistance. This study proposes a novel coarse alignment algorithm for b‐frame velocity‐aided SINS. The attitude is aligned with the optimisation‐based alignment method, and the alignment process is treated in the inertial frame, so the Coriolis effect can be partly excluded. Meanwhile, the position of SINS is updated in real time by rigorous dead reckoning method. Simulation and experimental results prove that the proposed method has a good performance in the dynamic coarse alignment of SINS.